The Mathematical Model Refinement of the Continuous Digging Machine and Its Research - Gerlici, Juraj; Kravets, Svyatoslav; Honchar, Mykhailo; Koval, Andrii (Manufacturing Technology Journal, 2020)
The article presents the results of theoretical research on creating the mobile continuous earthmoving machinery. The aim of the article is to develop and evaluate the effectiveness of technical decisions when creating and mod-ernizing trencher chain and bar actuators. The peculiarity of the performed research is a complex way to solve the problems of ensuring the efficient operation of the earthmoving machinery. It involves a combination of two subsystems: "soil - operating equipment" and "basic chassis ? bearing capacity of soil surface". The mechanisms of changing the power parameters of the machinery load are established. The input parameters for a system de-scribing the operation of a special earthmoving machinery are soil physical and mechanical characteristics and the dimensions of the earth excavation, the installed power of the basic chassis engine, the type and characteristics of transmissions of the machinery operating equipment and chassis propulsion, geometric parameters of single cutters, the speed of cutting the soil and moving the machinery. The mathematical model of the system as a whole makes it possible to determine the rational design, kinematic and energy characteristics of the machinery and its operating equipment. It minimizes the energy intensity of soil development.
Keywords: Mobile Continuous Earthmoving Machinery; Trencher; Speed Of Cutting The Soil; Kinematic Characteristics Energy Characteristics